The Moderating Role of State Attachment Anxiety and Avoidance Between Social Anxiety and Social Networking Sites Addiction. Issue 3 (June 2020) - Chen, Yunxiang; Li, Ruoxuan; Zhang, Peng; Liu, Xiangping
This study aims to explore the relationships among social anxiety, social networking sites (SNS) addiction, and SNS addiction tendency and further to examine the moderating role of state attachment anxiety and state attachment avoidance. A sample of Chinese young adults ( N = 437, Mage = 24.21 ± 3.25, 129 males) participated in this study, the data were collected through self-reports. Results revealed that participants' social anxiety was positively associated with SNS addiction and SNS addiction tendency. State attachment anxiety moderated these two relationships after controlling gender, age, and state attachment avoidance, while state attachment avoidance showed no significant moderating effect. Specifically, the positive relationships between social anxiety and SNS addiction (tendency) were restricted to individuals with low state attachment anxiety. While for individuals with high state attachment anxiety, social anxiety was no longer associated with SNS addiction or SNS addiction tendency. This study contributes to a deeper understanding of state attachment's moderating role in terms of the relationships between social anxiety and SNS addiction (tendency).